PENGARUH KOMPENSASI, WORK FAMILY CONFLICT DAN BEBAN KERJA TERHADAP KINERJA PERAWAT YANG SUDAH MENIKAH DI RSUD KABUPATEN BULELENG - Dina Apriliani, Ni Ketut; Novi Budiasni, Ni Wayan (Komunitas Manajemen Kompetitif, 2024)
This study aims to determine the effect of compensation, work family conflict and workload on the performance of married nurses in the Buleleng district hospital. The data collection technique used in this research was a questionnaire format using a Likert meter scale, and 71 married nurse respondents were selected. The data analysis technique used in this research is a multiple linear regression model known as SPSS statistics. The variables used in this research are compensation, work family conflict and workload on performance.The results of this study show that compensation has a positive and significant effect, with the result (9.262) being greater than the t-table (1.660). Work Family conflict has a negative effect (-2.189) and the tcount is greater than the t-table (1.660). Workload has a positive influence, with the result (2.287) having a t-count greater than the t-table (1.660).